Songs of the women trouvères - Doss-Quinby, Eglal, 1953- (Yale University Press, 2001)
This groundbreaking anthology brings together for the first time the works of women poet-composers, or trouvères, in northern France in the twelfth and thirteenth centuries. Refuting the long-held notion that there are no extant Old French lyrics by women from this period, the editors of the volume present songs attributed to eight named female trouvères along with a varied selection of anonymous compositions in the feminine voice that may have been composed by women. The book includes the Old French texts of seventy-five compositions, extant music for eighteen monophonic songs and nineteen polyphonic motets, English translations, and a substantial introduction.